The portrait of Abū l-Qāsim al-Baghdādī al-Tamīmī = Ḥikāyat Abī l-Qāsim al-Baghdādī al-Tamīmī - Abu-'l-Muṭahhar al-Azdī, Muḥammad Ibn-Aḥmad ca. 10./11. Jh (Gibb Memorial Trust, 2021)
"New translation and commentary on the 11th century tale of a Baghdadi party-crasher in Isfahan. It is introduced by its author as a microcosm of Baghdad. This work, written in prose but containing numerous poems, is widely hailed among scholars as a narrative unique in the history of Arabic literature, but The Portrait also reflects a much larger tradition of banquet texts, from Trimalchio's Dinner Party and Plato's Symposium to the works of Rabelais. It also paints a portrait of a party-crasher who is at once a holy man and a rogue, a figure familiar among scholars of the ancient Cynic tradition or other portrayals of wise fools, tricksters, and saints from literatures around the Mediterranean and beyond. While some early scholars of The Portrait dismissed it as disgusting and obscene, this work, with its wealth of material-cultural, philosophical, spiritual, and literary treasures, is much more than just a 'dirty book'.Following an introduction, which offers new insights into the relationship of the work to both its Greek predecessors and to its European descendants, the volume presents a new, improved edition of the Arabic text, together with a richly annotated translation, that aims at being both scholarly and readable, to some extent reflecting the often racy style of the Arabic. This should make it not only useful to specialists and students of medieval Arabic literature, but also accessible to a much wider general readership of those interested in comparative literature or 'world literature'. There are extensive indexes of names, places, subjects, and rhymes." --
Literaturverzeichnis Seite [460]-478
Contains facsimiles of orignal manuscript. Also include Index of persons and tribes; Index of place names; Index of selected Arabic and Persian words and terms; Index of verses in Arabic
Keywords: Azdī, Muḥammad ibn Aḥmad / Portrait of Abū l-Qāsim al-Baghdd̄i al-Tamīmī